Analisis Faktor Risiko Infeksi Saluran Kemih (ISK) Berdasarkan Diagnosis Dokter Umum di Puskesmas Tanralili Maros Tahun 2022-2023: Studi Retrospektif Cross Sectional: Analysis of Risk Factors for Urinary Tract Infection (UTI) Based on General Practitioner Diagnosis at the Tanralili Maros Community Health Center in 2022-2023: Retrospective Cross Sectional Study - Reza, Muhammad Alfi; Diennillah, Fathannia Rizky (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2024)
Abstract Background: Urinary Tract Infection (UTI) is a clinical condition in the urinary tract where there are bacteria in the urine caused by microorganisms that have the potential to enter the urinary tract. Urinary Tract Infections (UTI) often cause morbidity and can result in significant mortality. Although the urinary tract is normally free from bacterial growth, bacteria that generally rise from the rectum can cause UTIs. Aim: This study aims to explore the risk factors that influence the incidence of Urinary Tract Infections (UTI) at the Puskesmas Tanralili Maros. Methods: This research uses a cross-sectional retrospective descriptive method using total population sampling technique. Data was obtained through medical records for the 2022-2023 period at the Puskesmas Tanralili Maros and 96 medical records were obtained that were diagnosed with UTI by the general practitioner at the Community Health Center. Data processing was carried out using Microsoft Excel in 2016. Results: The results showed that the prevalence of UTI sufferers in 2022 was 8 people (39.58%) and in 2023 there was an increase of 58 people (60.42%). The highest prevalence of UTI was in the 26-45 year age range, 39 people (40.63%), and the lowest prevalence was in the <5 year age range, 1 person (1.04%). The highest prevalence of UTI was found in women as many as 69 people (71.88%) and in male patients as many as 27 people (28.13%). The highest prevalence of UTI in the education category was SMA (Senior High School), namely 38 people (39.58%), and the lowest prevalence was S2, 1 person (1.04%). The highest prevalence of UTI based on marital status was married patients, namely 73 people (76.04%) and the lowest prevalence was those with divorced status, 3 people (3.13%). The highest prevalence of UTI based on the occupation of housewives is the highest prevalence, namely 44 people (45.83), and the lowest prevalence of employment is not working, TNI and Police, namely 1 person each (1.04%) Conclusion: The prevalence of UTI sufferers in 2023 will increase compared to the previous year. The highest prevalence of UTI occurs in the age range 26-45, gender is female, education category is SMA (Senior High School), based on marital status is a married patient, based on occupation is a housewife